Anisotropic Magnetic Supraparticles with a Magnetic Particle Spectroscopy Fingerprint as Indicators for Cold-Chain Breach - Müssig, Stephan; Granath, Tim; Schembri, Tim; Fidler, Florian; Haddad, Daniel; Hiller, Karl-Heinz; Wintzheimer, Susanne; Mandel, Karl (ACS Applied Nano Materials, 2019)
Magnetic particle spectroscopy (MPS) is used in this work to obtain a magnetic fingerprint signal from anisotropic supraparticles, i.e., microrods assembled from superparamagnetic iron oxide nanoparticles. Exceeding its intended purpose of nanoparticle characterization for biomedical magnetic particle imaging, it is shown that MPS is capable of resolving structural differences between the anisotropic alignment of individual nanoparticles and its isotropic counterpart. Additionally, orientation-dependent MPS signal variations of anisotropic supraparticles are identifiable. This finding enables the detection of cold-chain breaches (for instance, during delivery of a product that needs to be cooled all of the time) by recording the initial and final MPS signals of microrod samples integrated into the container of a frozen product.
CRIS-Team Scopus Importer:2020-04-02
Keywords: cold-chain breach; detectors; magnetic particle spectroscopy; magnetic particles; magnetic sensor; supraparticles